Malária Grave Importada em Doentes Críticos - Palma dos Reis, Inês (2017)
Introduction: Imported malaria is a frequent diagnosis in Portugal, and in the most severe clinical forms it may present a high mortality rate. Material and Methods: We present seven cases of severe imported malaria, admitted to an intensive care unit between 2000 and 2010, with particular focus on risk factors, clinical presentation, treatment and results. Results: All patients had a history of recent travel to African endemic areas for malaria. Plasmodium falciparum was the agent isolated in all cases. Most patients had an inadequate prophylaxis. High parasitaemia in non-immune patients and treatment delay were associated with more severe clinical presentation. All the cases were complicated by organ failure, and three patients needed organ support and in two exchange blood transfusions were performed. There was one single death that was associated with marked delay in the initiation of therapy. Conclusion: In these patients, early and aggressive treatment, with a organ support in a critical care setting, allowed a good outcome with low mortality and no significant sequelae, despite the severity of presentation.